THE OPTIMIZATION OF PERFORMANCE OF THE PATROL UNITS OF SAMAPTA UNITS IN PREVENTING WILD RACING IN THE JEPARA POLICE JURISDICTION AREA - Muhammad Farhan Asyraf (Indonesian Journal of Police Studies, 2022)
Illegal racing is an activity that causes disturbances in public order and security. Jepara Regency is one of the regencies in Central Java Province that has cases of illegal racing has fluctuating numbers. This fluctuating number can be carried out by the National Police, namely by patrolling. The Patrol Unit of the Jepara Police Samapta Unit has problems in implementing performance and optimizing the performance of the Patrol Unit. This final project uses a qualitative approach with primary and secondary data sources at the Jepara Police. This final project uses the four previous theses as reference material in the research literature. Based on the results of the author's analysis, the novelty contained in this paper is about optimizing the performance of the Patrol Unit itself. Then, this Final Project uses management theory and SWOT as well as optimization, performance, patrol, and prevention concepts. Patrol Unit Samapta Unit has factual conditions which are real conditions in the field. The factual conditions are divided into two, namely initial conditions and influencing factors. The initial conditions of this writing are an explanation of the initial conditions supporting the implementation of the patrol, the factual conditions of the performance of the Patrol Unit, and the initial conditions of optimizing the performance of the Patrol Unit. Then, there are influencing factors, namely internal and external factors. Problem solving steps are the solutions given by the author to the two problems. The first solution regarding the performance of the Patrol Unit of the Samapta Unit is to have informants, coordinate with the Polsek Intelkam Unit, empower members of the dalmas, carry out dialogical patrols to the community, as well as provide handy talkies and create whatsapp groups. Then the solution to the second problem is to conduct trainings at the Jepara Police, create a police post, and arrange a re-patrol schedule. The conclusion of this final project is that the implementation of the Patrol Unit's performance and the form of Optimizing the Patrol Unit's performance is not optimal because the number of illegal racing is still fluctuating. So that the author, provides problem solving solutions to problems and suggestions.